TAX COMPLIANCE MODELING REGARDING INDIVIDUAL CHARACTERISTICS, INFORMATION TECHNOLOGY KNOWLEDGE AND SANCTIONS ON TAXPAYER AWARENESS, ABILITY, WILLINGNESS AND COMPLIANCE AS IMPACTS OF THE DEVELOPMENT OF THE CENTRAL BUSINES DISTRICT OF SURABAYA CITY - Tri Jarwa, Tri Ratnawati, Mulyanto Nugroho (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The purpose of this study is to analyze tax compliance modeling related to individual characteristics, knowledge of information technology and sanctions on the awareness, ability, willingness and compliance of taxpayers as the impact of the development of the central business district of Surabaya city. This study uses a qualitative and quantitative research approach or a mixed method research method. In this study, the sample size was 145 people. This study uses primary data by making direct observations, questionnaires, and interview guides (interviews). The technique used to collect primary data is preliminary survey, interview and questionnaire. The results show that the results of the measurement model analysis on the construct of individual characteristics explain that of the three indicators, all of them contribute significantly in shaping the individual characteristics of taxpayers. The indicator that has the greatest contribution in shaping the individual characteristics of taxpayers is the indicator that has the biggest factor loading, namely perception. Taxpayer knowledge does not positively affect taxpayer compliance and also proves that taxpayer interaction and knowledge of fraud have a positive effect on their tax compliance. So the implication of this research is that the tax authorities can apply tax laws which include tax penalties and penalties equally at each level of taxpayers and improve services in the taxation sector.